THE RESOURCES OF COMMERCIAL BANKS AND THEIR SYSTEMIC RISKS: THEORETICAL-METHODОLICAL ASPECTS(FEATURES) - Toyirov, Yu.A. (Educational Research in Universal Sciences, 2023)
The article describes the nature of systemic risks, which are of decisive importance in strengthening the resource base of commercial banks, and the forms of manifestation of systemic risks based on a critical analysis of theoretical and methodological approaches to its determination. In addition, the issues of identification and management of systemic risks, as well as the problems existing in this field, were considered.